Solid waste management service chain and sanitation safety: a case study of existing practice in Addis Ababa, Ethiopia - Shegaw Fentaye Sisay; Sirak Robele Gari; Sirak Robele Gari; Argaw Ambelu (Frontiers in Environmental Engineering)
BackgroundPoor sanitation safety in municipal solid waste management can cause environmental and public health problems. This is the case in Ethiopia, where the sanitation safety standards are low in the municipal solid waste management operations. Therefore, the sanitation safety practices along the solid waste management service chains in Addis Ababa, Ethiopia are poorly understood, and this research will contribute new insights for the scientific community and can also inform policies and the current solid waste management operations in Addis Ababa.Materials and MethodsThis study evaluated the safety of sanitation practices in the solid waste management service chain using a community-based approach in Addis Ababa city from January to August 2023. We have interviewed 384 participants using a cluster-random sampling technique and collected data through direct observations and face-to-face interviews. The study employed descriptive statistics, factor analysis and multiple linear logistic regression to analyze the data.ResultsThe findings of the study revealed significant variations in sanitation safety practices and risks among households during solid waste management. While 60% of households practiced solid waste segregation, only 15% of them followed safe segregation practices. The majority of households (85%) used unsafe segregation practices, such as mixing different types of waste and storing wet and dry waste together. Additionally, 85% of households used storage and transport containers that had leaks, potentially leading to contamination and infection. Furthermore, the study identified sanitation safety risks and practices at waste collection and transport sites. The risks included solid waste droppings during transport, inadequate vehicle cleaning and disinfection, lack of personal protective equipment (PPE) for workers, and uncovered waste collection vehicles, leading to environmental contamination. At transfer stations, the study found several risk factors, such as the lack of protection from animals and human activities, absence of shower facilities for workers, and inadequate storage facilities for PPE and tools. The transfer stations also lacked odor-neutralizing systems, proper waste handling practices, and physical fly barriers. Workers did not have the opportunity to shower after work, further increasing the risk. The sanitation safety practices and risks at solid waste treatment/disposal sites were also assessed. The study revealed medium risks associated with waste treatment/disposal operations, including working without PPE, handling contaminated containers and raw waste, and releasing airborne particulates that could be inhaled by workers or the nearby community. Factor analysis was conducted to categorize the variables related to sanitation safety practices. Six factors were identified, explaining approximately 60.6% of the overall variance. These factors represented different aspects of sanitation safety, including onsite waste handling practices, failure to maintain proper standards, risks related to unsafe waste storage, failure to properly store wastes at the household level, having safe storage practices, and unsafe waste segregation and storage. The study also examined the association between sanitation safety practices and sociodemographic factors using multiple linear regression analysis. Marital status, education, occupation, and income were found to be significant factors influencing sanitation safety practices during onsite waste handling. Income and marital status had the highest contribution, while occupation had the lowest contribution.Conclusion and Recommendationthe research findings highlight the wide variation in sanitation safety practices and risks associated with solid waste management. The study emphasizes the need for improved waste management practices at the household level, waste collection and transport sites, transfer stations, and waste treatment/disposal sites. The identified risk factors should be addressed through targeted interventions, including public awareness campaigns, proper training of waste management workers, and the implementation of safety protocols and infrastructure improvements. Additionally, sociodemographic factors play a role in determining sanitation safety practices, emphasizing the importance of considering these factors when developing waste management strategies and interventions.